Eye-tracked three-dimensional display based on laser backlight modulated by spatial light modulator - Zhang, Lei (2017)
Three-dimensional (3D) display technology is a fascinating research topic with wide applications such as 3D visual entertainment, 3D medical imaging and virtual reality, etc. However, the previous commercial solutions have various defects such as great loss of resolution, low brightness, fixed view location and the constraint of wearing special glasses. Glasses-free 3D displays providing 3D scene without any constraints are particularly attractive. In this thesis, two high-resolution autostereoscopic 3D displays are proposed and experimentally demonstrated. The first prototype is an eye-tracked laser-based 3D display, which is composed of a scanning laser, a ferroelectric liquid crystal spatial light modulator (FLC-SLM) array and a transmission screen. In this proposed system, the scanning laser backlight is modulated by the FLC-SLM array to generate directional backlight. Employing eye tracking technology, the directional backlight is projected on the location of viewers’ eye pupils in real-time, which allows multi-viewers to move freely. A prototype system has been set up to verify this idea. The experimental results show that the perceived 3D images have lossless fidelity, high brightness and contrast. The crosstalk of the 3D contents is below 5% which is well acceptable. Viewers can move freely in a wide zone to watch 3D contents without wearing any glasses. In the second prototype, we proposed a time-sequential LED-based 3D display, consisting of a high-density LED lens array, linear Fresnel lens and a low diffraction LCD. The LED lens array controls the direction of the backlight, which projects convergent viewing zone for viewer’s left and right eyes. A prototype has been established to verify this idea. The experimental results demonstrate a full-resolution 3D contents with natural 3D effect high contrast ratio around 300:1 and low crosstalk around 14%.